PERTANGGUNGJAWABAN PIDANA DALAM PRESPEKTIF HUKUM ISLAM DAN RELEVANSINYA TERHADAP PEMBAHARUAN HUKUM PIDANA INDONESIA - Murdiana, Elfa (Islamic University of Indonesia, 2012)
Revamping and restructuring of national law have implications for criminal law reform in Indonesia where, in the progress of change also affects the renewal of the concept of criminal responsibility which has to accommodate the legal values that live in the community as a mandate of Chapter IV of MPR No.IV/MPR/1999 item a.2. acts as a concrete manifestation of an intention and awareness owned offender will result from the actions of known perpetrators are conditions that must exist in the criminal law in the Islamic perspective on the implications of the Criminal Code Upcoming concept also embraces the same principles that can be said that the concept of criminal responsibility in Islamic law is relevant to the law in Indonesia pembangunan khususnya the upcoming renewal of the Criminal Code. Keywords: Pertanggungjawaban Pidana, Hukum Pidana, dan Hukum Islam.